A Pragmatic Analysis On Apology Strategies Used Steve Harvey In Announcing The Winner Of Miss Universe 2015 (LPPM Universitas HKBP Nommensen, 2023)
This research aims to find out what strategy apology Steve Harvey employed when he announced Miss Universe 2015 in the video clarification mistake announcement and what strategy is dominant used by Steve Harvey in video. This data was analyzed using the theory of the types of apology strategies from Trosborg (1995). The data in this study is an explanation video made by Steve Harvey for the mistake in announcing the winner of Miss Universe 2015, the video is taken from YouTube. In analyzing the data, the researcher took several steps. Namely: identifying data, explaining data, and drawing conclusions. The results of this study indicate that there are five types of apology strategies used by Steve Harvey in announcing the winner of Miss Universe 2015. , the number of evasive strategies is 8 data (33.33%), indirect apology is 11 data (43.83%), direct apology is 2 data (8.33%), remedial support is 1 data (4.16%) ), and opting out strategies as much as 2 data (8.33%). All repair support sub-strategies used by Steve Harvey aim to repair the damage caused by Steve Harvey's mistake.